Religious Mediatization: A Shift in Hanan Attaki’s Da’wa Practice in Digital Space - Fabriar, Silvia Riskha; Sulthon, Muhammad (Jurnal Dakwah Risalah, 2025)
This study analyzes the shift in Hanan Attaki’s da’wa practices through the phenomenon of religious mediatization, based on Stig Hjarvard’s theory of religious mediatization. In the digital era, da’wa develops beyond physical space through social media platforms and other digital channels. Research data were obtained by observing content on Hanan Attaki’s official accounts, such as YouTube, Instagram, and other digital platforms, and interviews with offline study participants who follow her da’wa activities. The results show that the mediatization of religion allows for significant changes in preaching in terms of format, message, and interaction with the audience. Hanan Attaki uses modern approaches relevant to popular culture to reach the younger generation. In this context, Hanan Attaki makes the media a tool for dissemination and a space for reconstructing religious practices. This research provides insight into how the mediatization of religion changes the method of da’wa and creates a new space for the development of religion in the digital era and strengthening the relevance of da’wa in modern society.